Pengaruh Pembiayaan Kredit KUR Mikro dan Pendapatan Nasabah terhadap Akad Murabahah pada BSI KC Kutacane - Anggita Anggita; Etty Harya Ningsi; Selvi Aristantya (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of Micro People's Business Credit (KUR) financing and customer income levels on the effectiveness of Murabahah contract implementation at Bank Syariah Indonesia (BSI) Kutacane Branch Office. This quantitative explanatory study involved 67 micro-customer respondents selected through a simple random sampling technique. Primary data were collected using a structured Likert-scale questionnaire and analyzed using multiple linear regression. The statistical results indicate that Micro KUR financing and real customer income have a positive and significant effect on the adoption and sustainability of Murabahah contracts, both partially and simultaneously. These two variables account for 70.4% of the variance in the contract's success. Affordable capital intervention strengthens business liquidity, while stable income serves as a risk cushion that ensures financial confidence and repayment capacity. The study concludes that the expansion of Islamic financial inclusion cannot rely solely on government funding but must synergize with the customers' organic financial capacity. The managerial implication recommends that banks restructure their credit scoring systems to focus more on real income ratios. This approach is projected to minimize default risks, maintain portfolio quality, and accelerate local community welfare in accordance with Islamic economic principles.